Altered regional homogeneity in post-traumatic stress disorder： a resting-state functional magnetic resonance imaging study - Yin, Yan; Jin, Changfeng; Eyler, Lisa T; Jin, Hua; Hu, Xiaolei; Duan, Lian; Zheng, Huirong; Feng, Bo; Huang, Xuanyin; Shan, Baoci; Gong, Qiyong; Li, Lingjiang (Neuroscience bulletin, 2012)
Objective Little is known about the brain systems that contribute to vulnerability to post-traumatic stress disorder （PTSD）. Comparison of the resting-state patterns of intrinsic functional synchronization, as measured by functional magnetic resonance imaging （fMRI）, between groups with and without PTSD following a traumatic event can help identify the neural mechanisms of the disorder and targets for intervention. Methods Fifty-four PTSD patients and 72 matched traumatized subjects who experienced the 2008 Sichuan earthquake were imaged with blood oxygen level-dependent （BOLD） fMRI and analyzed using the measure of regional homogeneity （ReHo） during the resting state. Results PTSD patients presented enhanced ReHo in the left inferior parietal lobule and right superior frontal gyrus, and reduced ReHo in the right middle temporal gyrus and lingual gyrus, relative to traumatized individuals without PTSD. Conclusion Our findings showed that abnormal brain activity exists under resting conditions in PTSD patients who had been exposed to a major earthquake. Alterations in the local functional connectivity of cortical regions are likely to contribute to the neural mechanisms underlying PTSD.